Moiré superlattice-level stick-slip instability originated from geometrically corrugated graphene on a strongly interacting substrate. (28th April 2017) - Shi, Ruoyu; Gao, Lei; Lu, Hongliang; Li, Qunyang; Ma, Tian-Bao; Guo, Hui; Du, Shixuan; Feng, Xi-Qiao; Zhang, Shuai; Liu, Yanmin; Cheng, Peng; Hu, Yuan-Zhong; et al.
Abstract: Two dimensional (2D) materials often exhibit novel properties due to various coupling effects with their supporting substrates. Here, using friction force microscopy (FFM), we report an unusual moiré superlattice-level stick-slip instability on monolayer graphene epitaxially grown on Ru(0 0 0 1) substrate. Instead of smooth friction modulation, a significant long-range stick-slip sawtooth modulation emerges with a period coinciding with the moiré superlattice structure, which is robust against high external loads and leads to an additional channel of energy dissipation. In contrast, the long-range stick-slip instability reduces to smooth friction modulation on graphene/Ir(1 1 1) substrate. The moiré superlattice-level slip instability could be attributed to the large sliding energy barrier, which arises from the morphological corrugation of graphene on Ru(0 0 0 1) surface as indicated by density functional theory (DFT) calculations. The locally steep humps acting as obstacles opposing the tip sliding, originates from the strong interfacial electronic interaction between graphene and Ru(0 0 0 1). This study opens an avenue for modulating friction by tuning the interfacial atomic interaction between 2D materials and their substrates.